The central role of provider training in implementing resource‐stratified guidelines for palliative care in low‐income and middle‐income countries: Lessons from the Jamaica Cancer Care and Research Institute in the Caribbean and Universidad Católica in Latin America. (29th April 2020) - Stoltenberg, Mark; Spence, Dingle; Daubman, Bethany‐Rose; Greaves, Natalie; Edwards, Rebecca; Bromfield, Brittany; Perez‐Cruz, Pedro E.; Krakauer, Eric L.; Argentieri, M. Austin; Shields, Alexandra E.
Abstract : Individuals in low‐income and middle‐income countries (LMICs) account for approximately two‐thirds of cancer deaths worldwide, and the vast majority of these deaths occur without access to essential palliative care (PC). Although resource‐stratified guidelines are being developed that take into account the actual resources available within a given country, and several components of PC are available within health care systems, PC will never improve without a trained workforce. The design and implementation of PC provider training programs is the lynchpin for ensuring that all seriously ill patients have access to quality PC services. Building on the Breast Health Global Initiative's resource‐stratified recommendations for provider education in PC, the authors report on efforts by the Jamaica Cancer Care and Research Institute in the Caribbean and the Universidad Católica in successfully developing and implementing PC training programs in the Caribbean and Latin America, respectively. Key aspects of this approach include: 1) fostering strategic academic partnerships to bring additional expertise and support to the effort; 2) careful adaptation of the curriculum to the local context and culture; 3) early identification of feasible metrics to facilitate program evaluation and future outcomes research; and 4) designing PC training programs to meet local health system needs. Abstract : The objective of this review is to provide a practical and stepwise approach for how individual palliative care leaders in low‐income and middle‐income countries can successfully develop and implement provider education programs. This approach includes: 1) fostering academic partnerships; 2) careful adaptation of the curriculum to the local context and culture; 3) early identification of metrics to make program evaluation and outcomes research possible; and 4) designing palliative care training programs to meet local health system needs.